In-Vitro Antibacterial Evaluation of Hawan Ash: A Traditional Material with Emerging Therapeutic Potential - Patel, Happy; Chandawat , Deepika; Patel , Mahek (Journal of Drug Delivery and Therapeutics, 2025)
Ash derived from ritualistic fire offerings has been traditionally considered to possess medicinal properties, yet its antibacterial potential remains scientifically unexplored. The lack of systematic evaluation necessitates an in-depth investigation of its efficacy. This study comprehensively examines the antibacterial activity of Hawan ash, assessing the influence of ash type, solvent selection, and dosage on bacterial inhibition to provide insights into its potential as a natural antimicrobial agent. Hawan ash extracts were prepared using different ash types (HA-1, HA-2 and HA-3) and solvents and tested at various concentrations against multiple bacterial species. Antibacterial activity was evaluated using the agar well diffusion method by measuring the zone of inhibition (ZOI). Results revealed significant variability in antibacterial activity depending on ash type, solvent, and dosage. Although standard antibiotic (Neomycin 30µg/disc) as a positive agent exhibited the highest ZOI (23.21 ± 0.06 mm), confirming the effectiveness of conventional antibiotics. Methanol ash extracts showed stronger activity than aqueous extracts (p < 0.05) with the highest inhibition against S. typhi (18.33 ± 0.29 mm at 0.6g/mL, HA-2). Aqueous extracts exhibited moderate activity with P. vulgaris being the most susceptible (10.00 ± 0.51 mm at 0.6g/mL, HA-1). These findings highlight the antibacterial potential of Hawan ash, influenced by extraction parameters. The observed variability underscores the need for advanced phytochemical profiling to identify bioactive constituents and optimize formulations for therapeutic applications.Keywords: Hawan ash, Antibacterial activity, Well diffusion method, ZOI, Therapeutic potential